Gene Diversity In Seed Crop Of Taurus Cedar (Cedrus Libani A. Rich.) Over An Altitudinal Range - N. Yazici; T. P. Novikova; A. I. Novikov; N. Bilir (Geography, Environment, Sustainability)
There could be many environmental and biological impacts such as edaphic, geographic, climatic, age, tree structure and population on morphological, physiological and genetically seed quality in plant species. Gene diversity is an important mirror of genetically seed quality. Gene diversity in seed crops were estimated based on female and male strobili productions of fifty trees (N) randomly chosen from each population sampled over an altitudinal range as low (1200-400 meters ≤ altitude), middle (1400 m < altitude ≤ 1600 m), high (1600 m < altitude ≤ 1800 m), and very high (1800 m < altitude) in Taurus cedar also known as cedar of Lebanon (Cedrus libani A. Rich.) for two consecutive years (2021&2022). The variation in strobilus production was subjected to estimation of female and male fertility variation. The total fertility variation (Ψ) was estimated from the female and male fertility variation. Impacts of some growth characteristics (tree height and diameter at breast height) on strobili productions were also investigated. Strobili productions varied among the populations and individuals within population, and between years. The differences for populations and years were also found for coefficient of variations which were mirror of fertility variation of the strobili productions. Tree height and diameter at breast height seemed more reasonable predictor than age for number of strobili. Fertility variations of female parents were generally higher than that of male in both years. First year showed generally higher parental variations in individual populations. Gene diversity (GD=1-0.5Ψ/N) ranged from 0.967 to 0.974 for the populations and years. The loss of highest gene diversity was 0.004 in low population (0.967 & 0.971) between years. Results of the study indicated that altitudinal gene diversity of seed crop could be used to produce genetically quality seed and their grading. Moreover, data sets can be used to fill the Forest Landscape Restoration library (FLR-Library).